Cyber Literacy Skills of Estonians: Activities and Policies For Encouraging Knowledge-Based Cyber Security Attitudes - Kont, Kate-Riin (Information & Media, 2023)
With the advent of COVID-19, people spent more time at home. Countries, societies, companies and individuals suddenly became dependent on cyberspace overnight. Work, shopping and leisure meant we became more than ever weak to the risks of cyberspace. The human factor makes people the “key” to otherwise technically hardly penetrable systems – criminals play on people’s greed, emotions, happiness, etc.It is no surprise that Estonians are more active daily internet users compared to the rest of the Europeans. But what is being done in Estonia at the national level, as well as in cyber protection organisational level, to raise the awareness of residents about cyber security? What else should be done to reduce victims among ordinary citizens and how to protect various important public and private organisations from the consequences of the cyber-risky behaviour of their employees? What is the role of libraries in promoting cyber security awareness? A human error is a central target of cyber attacks, phishing scams, and data breaches. Cyber criminals are becoming more and more inventive. It is important to understand that cyber security risks can be managed and mitigated, but not completely eliminated. Increasing security awareness is the only factor that can help limit breaches caused by human frailty.